Operative treatment for adenomyosis: update on literature review - Winata, Gde Sastra; Suardika, Anom; Mahayasa, Putu Doster; Budiana, Nyoman Gede; Kamajaya, I Gusti Ngurah Agung Trisnu (Indonesian Journal of Perinatology, 2024)
Adenomyosis, a condition characterized by the presence of endometrial tissue within the myometrium, poses significant challenges in diagnosis and management due to its widespread and infiltrative nature. Operative treatment remains the primary treatment of choice for patients with symptomatic adenomyosis, especially those seeking fertility preservation or uterine conservation. This review explores the latest surgical techniques, emphasizing the balance between effective lesion removal and preservation of uterine function. Techniques such as asymmetric dissection, wedge resection, and various flap methods are discussed, highlighting their role in minimizing the loss of healthy myometrium while preserving uterine integrity. The evolution of laparoscopic and robotic approaches has improved accuracy and recovery, while innovative procedures such as the PUSH operation offer improved structural healing after excision. The choice of technique is guided by preoperative imaging and intraoperative findings, tailored to the extent and location of adenomyosis involvement. This review underscores the importance of individualized surgical strategy in achieving optimal outcomes in the surgical management of adenomyosis.